Bring out the best in every employee [ how to engage your whole team by making every leadership moment count - Brown, Don , 1956-; Hawkins, Bill , 1947- (McGraw-Hill, 2012)
"Drive business growth and real value by empowering the right people in any organizationIn Bring out the Best in Every Employee, behavioral experts and top global consultants Don Brown and Bill Hawkins deliver a proven, research-supported program for developing what they call an organizations "solid citizens"--The employees at the widest part of the bell curve. Brown and Hawkins surveyed more than 40,000 workers to learn what employees want from their managers. Through analysis of their research findings, the authors have developed actionable strategies that leaders can use to empower and engage the "true heart of the team," as well as methods for tapping into this potential to achieve a powerful competitive edge in this post-recession rebound. Don Brown is the owner and founder of Situational Services, Inc., a training and development company. Don is also a founding developer of the successful Vision to Results concepts and products. Bill Hawkins is an internationally respected expert in leadership effectiveness who coaches organizations and individuals on ways to develop leadership potential. He is member of the Learning Network, and the Peter Drucker Foundation "Thought Leaders Forum.''